COVID-19 MEDIA DISCOURSE AND STIGMA: INSIGHTS INTO FOOD AVOIDANCE AND TRAVEL INTENTIONS - Mahmoud Ramadan AL-AZAB; Zakaria ELKHWESKY; Sawsan Haider Abdullah KHREIS (Geo Journal of Tourism and Geosites)
Stigma has grown in importance as a concept for understanding consumer behaviour during crises and gaining insights into post-pandemic food and travel intentions. While previous studies examined stigma from the perspective of stigmatised individuals, the current study investigated stigma from the perspective of other societies and their willingness to visit stigmatised countries or dine at stigmatised restaurants. The main aim of the current paper was to analyze the effect o f stigma associated with COVID-19 on travel intentions to stigmatised countries and food avoidance at stigmatised restaurants. It also examined the effect of media discourse on stigma. A number of 593 questionnaires from Egyptians and structural equation modelling (SEM) were used to test the model. The findings showed that stigma associated with COVID-19 has a significant and negative effect on travel intentions to stigmatised countries, while stigma has a significant and positive effect on avoiding dining at stigmatised restaurants. Additionally, media discourse significantly contributes to the stigma associated with COVID-19. On the other hand, there was no significant impact of food avoidance at stigmatised restaurants on the intention to travel to stigmatised countries. COVID-19-related discrimination and stigma must be stopped, and the media should enhance awareness without raising anxiety. The current research provided important insights that can be used to help revitalise the travel and food industries and to combat stigma-related prejudice.